Relación entre las características sonográficas y la estadificación TI-RADS en la decisión de realizar una biopsia. - Montiel-Islas, Anabel; Licea-Medina, David (Anales de Radiologia, Mexico)
Introduction: Indication of a biopsy in thyroid nodules can be determined by ultrasonographic images; its number is less when it is carried out by a capable radiologist. TI-RADS (Thyroid Imaging Reporting and Data System) staging can favor diagnostic evaluation. Objective: To analyze echographic characteristics of thyroid nodules and their staging with TI-RADS criteria at the time of deciding the perform of a biopsy. Patients and methods: Fiftyeight patients sent for thyroid ultrasound study, with or without indication of performing a biopsy. Ultrasonographic characteristics were determined before and after TI-RADS criteria. Results: Biopsy was performed in 30 patients (51.7%). According to pre-TI-RADS criteria, radiology service indicated the procedure to eight patients (26.6%). Six patients with high risk (three confirmed cases, 50%) and two with moderate risk (both benign). Other four cases with high risk, five moderate and 12 with low risk. Biopsies were performed to these patients by indication of treating doctor; all of them with benign disease. All the patients without biopsy (five with high risk, one moderate, and 21 with low risk) evolved as benign disease. At re-classification with TI-RADS, only three cases with cancer were classified as 5; three with TI-RADS 4 and two with TI-RADS 3 fulfilled criteria for biopsy and the result was of benignity. Fifty out of 58 patients (86.2%) didn't merit the performing of a biopsy. Conclusions: With pre-TI-RADS criteria, biopsies are over indicated, even though, in less possibility if indication was done by a capable radiologist. We suggest the support of a radiologist with evaluation of TI-RADS at deciding the perform of a biopsy in thyroid injuries in order to diminish costs and other inconveniences for the patients.